PENGARUH SALES GROWTH (SG), CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), TOTAL ASSETS TURN OVER (TATO), RETURN ON ASSETS (ROA) TERHADAP PRICE TO BOOK VALUE (PBV) (Studi Pada PT Indofarma Tbk. Yang Terdaftar Di BEI Periode 2012-2019) - Yoyo Sudaryo; Dyah Purnamasari; Nunung Ayu Sofiati; Astrin Kusumawardani (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2020)
ABSTRACT: Investors' consideration in investing, one of which is a high Company Value, where the value of one company is measured by Price to Book Value (PBV). Likewise, PT Indofarma Tbk, a company that was the subject of research, in the 2012-2019 period, the value of the company tended to increase, which was thought to be caused by Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER) variables, Total Assets Turn Over (TATO), Return On Assets (ROA). The purpose of this study was to determine the Effect of Sales Growth (SG), Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) to Price to Book Value (PBV). The method used is descriptive and verification methods. With secondary data type sourced from www.idx.co.id. Analysis techniques used to answer the problem formulation of Sales Growth (SG), Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) and Price to Book Value (PBV) using descriptive analysis and correlation analysis (R). The results showed that: 1) Average PBV value 8.33 times, 2) Average value of SG 5.13%, 3) Average value of CR 140.94%, 4) Average value of 127.73% DER, 5) Average value average TATO 1.14%, 6) Average ROA value of 0.14%. Based on a partial verification analysis 7) SG has a negative and not significant effect on PBV with a correlation value of -0.563, 8) CR has a negative and insignificant effect on PBV with a correlation value of -0,660, 9) DER has no significant positive effect on PBV with a correlation value of 0.141, 10) TATO has a significant negative effect on PBV with a correlation value of -0.233, 11) ROA has no significant positive effect on PBV with a correlation value of 0.055. Based on simultaneous verification analysis 12) Sales Growth (SG), Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) have a not significant positive effect on Price to Book Value (PBV) with a correlation value of 0.643. Keywords: Price to Book Value (PBV), Sales Growth (SG), Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) ABSTRAK: Pertimbangan investor dalam melakukan investasi, salah satunya adalah Nilai Perusahaan yang tinggi, dimana nilai perusahaan yang salah satunya diukur dengan Price to Book Value (PBV). Demikian pula dengan PT Indofarma Tbk perusahaan yang menjadi subjek penelitian dimana pada periode 2012-2019 nilai perusahaannya cenderung meningkat yang diduga disebabkan oleh variabel Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA). Tujuan penelitian ini untuk mengetahui Pengaruh Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) terhadap Price to Book Value (PBV). Metode yang digunakan adalah metode deskriptif dan verifikatif. Dengan jenis data sekunder yang bersumber dari www.idx.co.id. Teknik analisis yang digunakan untuk menjawab rumusan masalah Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) dan Price to Book Value (PBV) menggunakan analisis deskriptif dan analisis korelasi (R). Hasil penelitian menunjukan bahwa : 1) Nilai Rata-rata PBV 8.33 Kali, 2) Nilai Rata-rata SG 5.13%, 3) Nilai Rata-rata CR 140.94%, 4) Nilai Rata-rata DER 127.73%, 5) Nilai Rata-rata TATO 1.14%, 6) Nilai Rata-rata ROA 0.14%. Berdasarkan analisis verifikatif secara pasrsial 7) SG berpengaruh negatif dan tidak signifikan terhadap PBV dengan nilai korelasi -0,563, 8) CR berpengaruh negatif dan tidak signifikan terhadap PBV dengan nilai korelasi -0,660, 9) DER berpengaruh positif tidak signifikan terhadap PBV dengan nilai korelasi 0,141, 10) TATO berpengaruh negatif tidak siginifikan terhadapm PBV dengan nilai korelasi -0,233, 11) ROA berpengaruh positif tidak signifikan terhadap PBV dengan nilai korelasi 0,055. Berdasarkan analisis verifikatif secara simultan 12) Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA) berpengaruh positif tidak signifikan terhadap Price to Book Value (PBV) dengan nilai korelasi 0,643. Kata Kunci : Price to Book Value (PBV), Sales Growth (SG), Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Assets (ROA)